Effects of altitude and microclimate on the distribution of ferns in urban areas - Othman, Rashidi; Mohd Latiff, Nur Hanie; Tukiman, Izawati; Hashim, Khairusy Syakirin Has-Yun (Universiti Teknologi Malaysia, 2015)
The aim of the research is to explore the potential of fern species as natural ecological indicator agent to forecast microclimate changes in the urban area. Ferns which also known as pteridophyte are not only valuable in term of its ethno-botanical uses such as food and medicine but also useful in ecological values. Other than that it can be used to treat unhealthy environment such as absorbing methane gas, fertilizing land and treating heavy metal such as arsenic as well as can be used as a potential ecological indicator agent for microclimate changes. In this research, observation and measurement were made at two different environments which are natural environments; Gunung Jerai, Kedah and Lata Jarum, Pahang and manmade setting environments; Hospital Serdang, Serdang and Secret Garden, Kuala Lumpur. Interestingly results from two case studies of natural environments indicated that the distribution and abundance of fern species strongly influenced by differences in altitude. Twelve fern species were found at different elevations at Gunung Jerai, Kedah whereas 20 fern species were found at Lata Jarum, Pahang. Among the species found at Gunung Jerai were Selaginella willdenowii, Arcypteris irregularis, Adiantum caudatum, Pityrogramma calomelanos, Histiopteris stipulacea, Athyrium cordifolium, Osmund wachellii, and Cyathea contaminans. Whereas the species found at Lata Jarum are Dicranopteris linearis, Phymatodes scolopendria, Antrophyum callifolium, Arcypteris irregularis, Phymatodes crustachea, Selaginella willdenowi, Angiopteris evecta and Aglaomorpha heraclea. Another factor that influences the occurrences of the fern species is microclimate particularly atmospheric factor. Results observed from both case studies showed that light intensity, relative humidity and temperature also influenced the distribution of fern species. Therefore fern species are excellent ecological indicator which can be used as phytoindicator for unhealthy environment such as harsh environment or to predict microclimate changes at urban area.